Organic Synthesis via Transition Metal-Catalysis - Gabriele, Bartolo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book collects articles published in a Special Issue of Molecules entitled "Organic Synthesis via Transition Metal-Catalysis". Transition metal catalysis is a powerful methodology for the direct synthesis of functionalized, high value-added molecules by the assembly of simple units in one step, and is acquiring increasing importance in modern organic synthesis. The book presents seven papers overall, two reviews and five original research articles, dealing with Pd-catalyzed arylation, Rh-catalyzed synthesis of organosulfur compounds, Rh-catalyzed reductive hydroformylation, V-catalyzed oxidation of hydrocarbons, and Zn-, Pd- and Rh-catalyzed cyclization processes, leading to heterocyclic derivatives.